Digital Transformation in Higher Education: Enhancing Support Services Through Mobile Apps - Anusuyah Subbarao; Nasreen Khan; Aysa Siddika; Muhammad A. Fathullah; Mohd A. Sanwani; Fia F. Adam; Debrina V. Ferezagia; Melisa B. Altamira (HighTech and Innovation Journal)
The fourth industrial revolution has considerably enhanced technology, resulting in disruptive developments across various industries, including higher education. Generation Z, known as digital natives, has specific digital preferences, making mobile applications essential for improving their educational experience. The present study aims to investigate the digital transition in higher education, emphasizing using mobile applications as campus support services for Generation Z students. The study investigates the factors influencing mobile app acceptance and usage, intending to enhance educational support services' efficiency and quality among 100 students from different universities. By performing multiple linear regression, the study revealed that perceived usefulness is the most critical factor driving students' intention to use mobile apps in higher education. In contrast, other elements such as ease of use, competence, accessibility, and data privacy were not deemed significant concerns by the students. The findings are intended to advise higher education institutions on integrating mobile apps to assist Generation Z better, eventually leading to increased student engagement and satisfaction. This study emphasizes the significance of mobile technology in current educational contexts and offers practical insights for universities looking to use digital technologies to improve campus support services. However, the outcome may vary for students from different demographic and socio-economic backgrounds.